Lithium Ion Batteries: Ionic Liquid‐Assisted Anchoring SnO2 Nanoparticles on Carbon Nanotubes as Highly Cyclable Anode of Lithium Ion Batteries (Adv. Mater. Interfaces 14/2020). Issue 14 (27th July 2020) - Liu, Kuiming; Zhu, Shengming; Dong, Xufeng; Huang, Hao; Qi, Min
Abstract : In article number 1901916 by Xufeng Dong, Min Qi, and co‐workers, ionic liquid assisted strategy is proposed to construct hybrid nanostructure with the SnO2 uniformly and strongly grafting on the carbonnanotubes (CNTs). The strategy is beneficial to strengthen the interface interaction between SnO2 and CNTs and facilitates the electron/ion transport in SnO2 . When served as an anode for lithium ion batteries, SnO2 @IL‐CNTs exhibits excellent electrochemical performance.